(untitled) (Bangladesh Journal of Botany, 2014)
Eight newly recorded phtyoplankton belonging to the algal Order Volvocales, Chlorococcales, Penales and Cryptomonadales from Bangladesh have been described in the present paper. The taxa are Collodictyon sparsavacuolatum Skuja, Tetrachloridium carteroides (Pascher et Jha) Huber-Pest., Chlamydomonas bicilliata Korsch., Chlorogonium liostracum Strehlow, Asterarcys cubensis Comas, Nitzschia hybrida Grun., Rhodomonas lens Pascher and Ruttner and R. ovalis Nygaard. DOI: http://dx.doi.org/10.3329/bjb.v43i1.19753 Bangladesh J. Bot. 43(1): 87-90, 2014 (June)